PENINGKATAN PENGETAHUAN SANTRI PESANTREN MELALUI PELATIHAN PEMBUATAN SABUN CUCI PIRING DALAM PEMANFAATAN LIMBAH KULIT NENAS - Indah Sari, Vonny; Jenika Putri, vivin; Rahmah, Anania; Ulfa Azzahro, Hanifah (Fakultas Pertania Universitas Muara Bungo, 2023)
Pineapple peel waste is generally not utilized properly and is considered waste that should be thrown away. In fact, from the results of phytochemical tests, pineapple skin contains flavonoid compounds, tannins and saponins and contains compounds that have the potential to be anti-bacterial. One use of pineapple peel waste is as the main ingredient in making dishwashing soap. Dish washing soap produced from processing waste from pineapple peels and lime slices has a fresh aroma and good washing power and is gentle on hands. The aim of this service is to increase the knowledge of the Hidayatul Mubtadiin Rumbai Islamic Boarding School community in utilizing pineapple peel waste which is widely scattered in Pekanbaru City, where pineapples are one of the mainstays of agricultural products produced from Pekanbaru, especially Kualu Nenas Village. With this training, it is hoped that the community can utilize pineapple waste into more useful products and furthermore, the students of the Hidayatul Mubtadiin Islamic Boarding School, Muara Fajar Timur Rumbai Village, can make their own dishwashing soap for the Islamic boarding school's daily needs and for sale